Original articleInhibition of mitochondrial complex II affects dopamine metabolism and decreases its uptake into striatal synaptosomes - Cąkała, Magdalena; Drabik, Jacek; Kaźmierczak, Anna; Kopczuk, Dorota; Adamczyk, Agata (Folia Neuropathologica, 2006)
The mitochondrial toxin, 3-nitropropionic acid (3-NP), is a specific inhibitor of succinate dehydrogenase, complex II in the mitochondrial respiratory chain. The aim of our study was to determine the relationship between inhibition of mitochondrial complex II and dopamine (DA) metabolism and its transport into rat striatal synaptosomes after exposure to 3-NP. The study was carried out using spectrophotometric, radiochemical and HPLC methods. Our data showed that inhibition of succinate dehydrogenase by intraperitoneal (i.p.) injection of 3-NP (cumulated dose 100 mg/kg in 4 days) significantly affected DA metabolism, leading to the accumulation of its metabolites, 3,4-dihydroxylphenylacetic acid (DOPAC) and homovanillic acid (HVA) in the rat striatum. These experimental conditions had no effect on free radical dependent lipid peroxidation in the brain. In vitro experiments revealed that DA and DOPAC significantly decrease lipid peroxidation in the brain homogenate. Moreover, 3-NP significantly inhibited [3H]DA uptake into striatal synaptosomes by specific dopamine transporter (DAT). The scavengers of superoxide radical (O2–) Tempol and Trolox had no effect on DAT function, but the nitric oxide synthase (NOS) inhibitor Nw-nitro-L-arginine (100 µM) prevented 3-NP-evoked DAT down-regulation. In summary, our results indicate that inhibition of mitochondrial complex II by 3-NP enhances DA degradation and decreases its uptake into synaptosomes. It is suggested that NO and energy failure are responsible for alteration of the dopaminergic system in the striatum. Abbreviations: 3-NP – 3-nitropropionic acid; DA – dopamine; i.p. – intraperitoneal; DOPAC – 3,4-dihydroxylphenylacetic acid; HVA – homovanillic acid; DAT – dopamine transporter; TBARS – Thiobarbituric acid reactive substances; NOS – nitric oxide synthase; MAO – monoamine oxidase; MDA – malondialdehyde; TCA – trichloroacetic acid